Kepemimpinan Kiai dalam Transformasi Pendidikan Pesantren di Era Disrupsi - Al Ayubbi, Syaefuddin Ahrom (Sahabat Akademia Group, 2024)
Pesantren is one of the oldest Islamic educational institutions in Indonesia, playing a crucial role in shaping students' religious understanding and character. However, in the disruption era, pesantren face significant challenges in maintaining their relevance amid rapid technological advancements and changing societal needs. This study aims to analyze the role of kiai leadership in transforming pesantren education to adapt to these challenges. Using a qualitative approach with a case study method, this research focuses on Pondok Pesantren Tahfidzul Qur’an Al-Asy’ariyyah Wonosobo, which has integrated traditional religious education with modern innovations. Data were collected through observation, documentation, and literature analysis. The findings indicate that kiai leadership is instrumental in balancing religious traditions with contemporary educational advancements, such as digital learning and structured pesantren management. The study implies that pesantren must embrace technological adaptation and curriculum development while preserving their core values. Future research should explore broader comparisons.